Knowledge of Sexual and Reproductive Health Rights Among University Students: A Cross-Sectional Study in Southeast Ethiopia - Kene C; Geta G; Ejigu N; Desta F (Dove Medical Press, 2023)
Chala Kene,1 Girma Geta,1 Neway Ejigu,1 Fikreab Desta2 1Madda Walabu University, School of Health Science, Department of Midwifery, Bale Goba, Ethiopia; 2Madda Walabu University, School of Health Science, Department of Public Health, Bale Goba, EthiopiaCorrespondence: Chala Kene, Email kenechala@gmail.comBackground: In many situations, it can still be challenging to talk about sexual and reproductive health rights, and the little scientific research available indicates that university students have a poor understanding of these issues. Therefore, the aim of this study was to assess the knowledge of sexual and reproductive health rights among university students in southeast Ethiopia.Methodology: From February to March 2022, 483 study participants took part in an institutionally based cross-sectional study. The study participants were chosen using a SRS method. EpiData version 4.6.2.0 was used to enter data, and SPSS version 26.0 was used to analyze it. A bivariate and multivariable binary logistic regression model was used to identify factors associated with SRHR knowledge. The odds ratio and a 95% confidence interval were used to calculate the significance level.Results: The optimal level of knowledge on SRHR was discovered to be 52.1% [95% CI (47.32– 55.08)] among university students in southeast Ethiopia. The multivariate binary logistic analysis indicated that being urban in the origin of residency [AOR=1.52, 95% CI (1.02– 1.14)], being a health student [AOR= 12.21, 95% CI (7.27– 14.88)], attending secondary school in private [AOR=6.12, 95% CI (1.02– 1.14)], accessibility of a RH club on campus [AOR=6.12, 95% CI (1.02– 1.14)] and participating in RH club [AOR=3.95, 95% CI (3.47– 5.90)] to be variables that are strongly related to the optimal level of knowledge.Conclusion and Recommendation: Four out of ten students had poor knowledge of SRHR. The variables associated with a high level of knowledge about SRHR were urban residency, health students, attending a private secondary school, the availability of a RH club on campus, and participation in a RH club. Including sexual education in the non-health department’s course, establishing RH clubs on campus, and encouraging participation of students in these clubs are recommended.Keywords: university students, knowledge, sexual and reproductive health privileges